(untitled) (Research, Society and Development, 2020)
Yeasts, especially the genus Rhodotorula, have the capacity to produce considerable amounts of compounds with high added value, such as carotenoid pigments and lipids, in addition to proteins. Thus, the objective of this work was to study the drying in foam layer (foam-mat drying) of the biomass of the yeast Rhodotorula glutinis to obtain the powder. The influence of temperature, concentration of sparkling wine and stirring time, drying time and final humidity was evaluated. The physical characterization of the foam was also evaluated: stability; density; air incorporation and expansion. The production of biomass from Rhodotorula glutinis (CTT 2182) had an average yield of 60 g per batch. In the physical characterization of the foam, the agitation time was responsible for the best results for density, volumetric expansion and air incorporation. The foam stability was favored by the increase in the concentration of the sparkling wine. In drying, temperature was the only variable that had an influence on drying time. In the physico-chemical characterizations of the biomass powder of the yeast Rhodotorula glutinis, an average theoretical yield was obtained for the experiments of the central point of 22.36%, an average ascorbic acid content of 41.36 mg / 100 g of powder and solubility greater than 20% in all conditions studied. In the analysis of water activity, all experiments obtained values above 0.6, thus ensuring the viability of the product produced. The drying process in foam- mat drying of the biomass of the yeast Rhodotorula glutinis proved to be viable.